Production of biodegradable poly lactic acid from pineapple industry wastewater by lactobacillus casei fermentation - Hassan, Saber Salem (2017)
Pineapple processing industry generates large amount of liquid waste, which contains high concentration of biodegradable organic, suspended solid and high biological oxygen demand (BOD), as well as carbohydrates such as glucose and fructose. The by-products effluent can be a substrate for production of value-added products by microbial fermentation such as biomaterial. However, investigation on the bioconversion of pineapple wastewater to value-added products is still lacking. The objective of this study is to produce biodegradable poly lactic acid (PLA) from pineapple industry waste water by Lactobacillus casei. The L. caseiwas cultivated with a medium containing extracted glucose for 24 h. The optimisation of cultural conditions (temperature, pH, inoculum size, nitrogen source) for lactic acid (LA) production was carried out. Purification of LA by reverse osmosis was done. After that, synthesize of PLA was achieved by direct polymerization of pure LA under a nitrogen atmosphere at an optimum time and temperature. Finally, the characterization of PLA was conducted by gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). A maximum production of 31.6 g/l LA was obtained at pH 6, 37 °C and 5% (v/v) of inoculum size. Interestingly, the concentration of pure LA was measured up to 54 g/l after purification. The optimum percentage yield of PLA obtained was 10.4% for 160 °C at 12 h and the molecular weight MW was in the range of 1000 Da to 5215 Da. The highly intense band of 2995 was due to CH stretching of the methylene and methyne groups, a range 1716 to 1748 for ester carbonyl group; other significant bands are in region 1118-1360 typical for ester group -CO-O. A clear glass transition (Tg)at 45.3 °C was exhibited when heat synthesis at 160°C. The results obtained confirmed the production of PLA. Hence it can be concluded that pineapple wastewater can be used for PLA production by L. casei under optimum conditions.